2005
DOI: 10.1007/s00220-004-1266-5
|View full text |Cite
|
Sign up to set email alerts
|

Factoriality of q-Gaussian von Neumann Algebras

Abstract: We prove that the von Neumann algebras generated by n q-Gaussian elements, are factors for n 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 5 publications
(10 reference statements)
1
51
0
Order By: Relevance
“…In the α = 0 case the factoriality was proved by Bożejko, Kümmerer and Speicher [14] and by Śniady [47] in special cases and then by Ricard [42] in full generality. Moreover Nou showed that vN(G 0,q (H R )) is not injective if dim(H R ) ≥ 2 [40].…”
Section: Traciality Of the Vacuum Statementioning
confidence: 92%
“…In the α = 0 case the factoriality was proved by Bożejko, Kümmerer and Speicher [14] and by Śniady [47] in special cases and then by Ricard [42] in full generality. Moreover Nou showed that vN(G 0,q (H R )) is not injective if dim(H R ) ≥ 2 [40].…”
Section: Traciality Of the Vacuum Statementioning
confidence: 92%
“…Recent works have been focused on the study of mathematical properties of q-Gaussian functions [70][71][72][73][74][75][76][77][78], including methods for generating random numbers which follow q-Gaussian distributions [79,80]. q-Gaussians have been employed in the study of a wide range of themes including probabilistic models [81,82], stellar plasmas [83], porous-medium equation [84], Bose-condensed gases [85][86][87], dynamical systems [88][89][90], polymeric networks [91], smallworld networks [92], fingering processes [93], processes with stochastic volatility [94,95] and nonlinear diffusion [96,97].…”
Section: Q-gaussian Distributionmentioning
confidence: 99%
“…known as the Touchard-Riordan formula [58,56,57,49]. No analogue of the above expression is presently known for the joint generating function of crossings and nestings.…”
Section: Next Let [N] Qt Denote the (Q T)-analogue Of A Positive Imentioning
confidence: 96%
“…For any Hilbert space H of dimension n 2, Γ q (H ) is a factor[13,53,48] and Γ 0 (H ) is isomorphic to the free group factor on n generators[61].…”
mentioning
confidence: 99%